A preliminary study on antimicrobial activity of Imperata cylindrica - Harun @ Ismail, Ahmad Fahmi; Abd. Samah, Othman; Sule, Abubakar (Faculty of Resource Science and Technology, Universiti Malaysia Sarawak, 2011)
Antimicrobial properties of the methanol, chloroform or polybutylene succinate (PBS) extracts of leaves and rhizome from Imperata cylindrica were investigated against five clinical isolates of bacteria, namely Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, Staphylococcus aureus and Candida albicans. In disc diffusion test the three types of extracts showed varied levels of antimicrobial activity against the tested isolates, with inhibition zones ranging from 6.33 ± 0.58 to 11.67 ± 8.14 mm diameters. The highest activity was exerted by the methanol leaves extract on P. aeruginosa (11.67 ± 8.14mm) at 50 mg/ml and the least activity was exerted by both the leaves and rhizome extracts of the plant at 1mg/ml on B. subtilis, P. aeruginosa, S. aureus and E.coli (6.33 ± 0.58mm) respectively. A minimum inhibitory concentration (MIC) value of 25mg/ml was obtained for the methanol, chloroform, PBS leaves or rhizome extracts on B. subtilis, P. aeruginosa, S. aureus and E. coli.